Shadow Education: Concept Analysis - Kačinskaitė-Urbonienė, Ieva (Pedagogika, 2025)
This paper presents the phenomenon of shadow education. The study aimed to analyse and conceptualise the concept of shadow education, to reveal the main characteristics, assumptions, and consequences of the concept, based on the analysis of scientific publications by Lithuanian and foreign authors, using data collection and data analysis methods. Based on Walker and Avant’s (2005) research strategy, it is revealed that shadow education is an interdisciplinary and complex phenomenon, encompassing all paid direct and indirect measures and activities, which are carried out outside of formal education, but within the framework of the formal curriculum. It also identifies the main characteristics of informal education as complementary, private, competitive, dependent on formal curriculum, compensatory, diverse in its forms, intensity, providers: flexible and adaptive; global; unregulated; and considered as an activity. The main prerequisites identified are the desire on the part of parents and children to improve their academic performance, to close learning gaps, to maintain or improve their social position in society, or, on the part of educators, to engage in profitable activities, to change the form of employment. Positive and negative consequences of informal education have been identified in terms of social inequalities, commercialisation of education, family relations, children’s development, and learning support.